Effectiveness of a novel cellular therapy to treat multidrug-resistant tuberculosis - Skrahin, Aliaksandr (J Clin Tuberc Other Mycobact Dis, 2016)
INTRODUCTION: We urgently need novel treatments for multidrug-resistant tuberculosis (MDR-TB). Autologous mesenchymal stromal cell (MSC) infusion is one such possibility due to its potential to repair damaged lung tissue and boost immune responses. We aimed to assess the effectiveness of MSC to improve outcomes among MDR-TB patients. METHODS: We analyzed outcomes for 108 Belarussian MDR-TB patients receiving chemotherapy. Thirty-six patients (“cases”) also had MSCs extracted, cultured and re-infused (average time from chemotherapy start to infusion was 49 days); another 36 patients were “study controls”. We identified another control group: 36 patients from the Belarussian surveillance database (“surveillance controls”) 1:1 matched to cases. RESULTS: Of the cases, 81% had successful outcomes versus 42% of surveillance controls and 39% of study controls. Successful outcome odds were 6.5 (95% Confidence Interval: 1.2–36.2, p = 0.032) times greater for cases than surveillance controls (age-adjusted). Radiological improvement was more likely in cases than study controls. Culture analysis prior to infusion demonstrated a poorer initial prognosis in cases, yet despite this they had better outcomes than the control groups. CONCLUSION: MSC treatment could vastly improve outcomes for MDR-TB patients. Our findings could revolutionize therapy options and have strong implications for future directions of MDR-TB therapy research.